Knowledge and attitude regarding febrile seizure among parents of under five children in Godawari municipality. - Gurung,Meenuka (2018)
ABSTRACT: Febrile seizure is the most common seizure in children worldwide. Between 1 and 4% of children develop febrile seizure within five years of life. The main purpose of this study is to assess parents' knowledge and attitude regarding febrile seizure in children. This study will be carried out among parents of children who are under five years in Thaiba-14, Lalitpur. A quantitative descriptive cross sectional research design will be used for the study. A purposive sampling method will be used. The sample size for this study will be 98. Data will be collected through structured interview method including socio- demographic information, questionnaire about knowledge on febrile seizure, febrile convulsion: parental KACP questionnaire. Then data will be analyzed by using descriptive statistics and inferential statistics. The result of this study will make clear about the knowledge and attitude regarding febrile seizure among parents of selected community in Godawari Municipality. Key words: Knowledge, Attitude, Parents, Febrile Seizure